2020
DOI: 10.1055/a-1209-3668
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Survival in Resected T4 Non-small Cell Lung Cancer: Is There Any Difference in the T4 Subgroups?

Abstract: Introduction The eighth edition of the TNM classification revised the subgroups of T4 non-small cell lung cancer (NSCLC). This study aimed to compare the T4-NSCLC subgroups that underwent surgical treatment in terms of mortality, morbidity, survival, and prognostic factors based on the new classification. Materials and Methods Between 2000 and 2014, a total of 284 T4-NSCLC patients who underwent lung resection (mediastinal organ invasion, n = 114; ipsilateral different lobe tumors, n = 32; and tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…4 Similarly, Aksoy et al's study with 284 T4 NSCLC cases who had surgery found 5.6% mortality and 23.9% morbidity rate. 5 Yamanashi et al's study investigating results of 93 cases stated 30-day mortality as 0%, with a complication rate of 56%. 2 Comparing with these studies' mortality and morbidity rates, it is possible to say that our mortality rate is similar, but a higher morbidity rate was observed.…”
Section: Discussionmentioning
confidence: 97%
“…4 Similarly, Aksoy et al's study with 284 T4 NSCLC cases who had surgery found 5.6% mortality and 23.9% morbidity rate. 5 Yamanashi et al's study investigating results of 93 cases stated 30-day mortality as 0%, with a complication rate of 56%. 2 Comparing with these studies' mortality and morbidity rates, it is possible to say that our mortality rate is similar, but a higher morbidity rate was observed.…”
Section: Discussionmentioning
confidence: 97%
“…The impact of non-size-based T4 features on survival in NSCLC patients with tumors >7 cm in size is controversial. 8,9 Another controversial issue is whether there is a survival difference between T4 cases classified based on tumor size or not. Ichinose et al 10 suggested that T4 tumors classified based on size should be treated differently from those not classified based on size.…”
Section: Discussionmentioning
confidence: 99%